QAR : A STRATEGY FOR TEACHING READING COMPREHENSION AT SENIOR HIGH SCHOOLS - Andri Defrioka (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2016)
Teaching students strategies for answering questions is an important part of comprehension instruction. The failure of students in comprehending the text was caused of misunderstanding the questions and how it relates to the answer. QAR is a reading comprehension strategy applicable to use with both fiction and nonfiction texts. It is a valuable skill for all students to obtain, especially struggling readers. QAR assists students in relating prior knowledge to text information. It becomes a conscious process students actively engage in when reading texts, especially difficult reading selections. With this strategy, students become aware of the relationships between questions and answers. Students will begin to understand where the answers come from and thus are better able to answer the questions correctly. This paper reveals an alternative model for teaching reading comprehension using QAR strategy. Hopefully, it will be useful for English teachers who are training students to read and face the implementation of Curriculum 2013 at senior high schools.